2017
DOI: 10.1002/lio2.90
|View full text |Cite
|
Sign up to set email alerts
|

Verbal working memory and inhibition‐concentration in adults with cochlear implants

Abstract: ObjectivesNeurocognitive functions contribute to speech recognition in postlingual adults with cochlear implants (CIs). In particular, better verbal working memory (WM) on modality‐specific (auditory) WM tasks predicts better speech recognition. It remains unclear, however, whether this association can be attributed to basic underlying modality‐general neurocognitive functions, or whether it is solely a result of the degraded nature of auditory signals delivered by the CI. Three hypotheses were tested: 1) Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 36 publications
6
48
1
2
Order By: Relevance
“…The question of whether cognitive skills might be a predictor of postoperative speech outcome has been discussed in the past with inconsistent results. 34 , 76 No correlation between preoperative cognitive abilities and postoperative speech performance in either quiet or in noise conditions was detected in our investigation, which is in contrast to the data shown by Heydebrand et al 77 or Moberly et al 78 …”
Section: Discussioncontrasting
confidence: 94%
“…The question of whether cognitive skills might be a predictor of postoperative speech outcome has been discussed in the past with inconsistent results. 34 , 76 No correlation between preoperative cognitive abilities and postoperative speech performance in either quiet or in noise conditions was detected in our investigation, which is in contrast to the data shown by Heydebrand et al 77 or Moberly et al 78 …”
Section: Discussioncontrasting
confidence: 94%
“…In listeners with cochlear implants, reaction times in an incongruent color Stroop task has been shown to correlate with speech recognition (Moberly, Houston, et al, 2017), which could reflect the role of inhibition in understanding speech with a cochlear implant. To test the possibility that this result will replicate in our listeners, we used the same Stroop task.…”
Section: Attentionmentioning
confidence: 99%
“…For example, a recent study found no relation between sentence recognition in speech-shaped noise for CI users and scores on a reading span task, but strong correlations were found for an auditory listening span task of WM. 48 However, in other populations of patients with lesser degrees of hearing loss, previous reports have found reading span to be correlated with speech recognition. 23,49 In the sample of CI users tested in this study, inhibitory control abilities did not contribute substantially to speech recognition in CI users, but did partially mediate aging effects on speech recognition in NH controls.…”
Section: Discussionmentioning
confidence: 94%